Fermions from time-dependent boundaries: stress-energy versus clicks of a particle detector - Wan Mokhtar, Wan Mohamad Husni (2019)
In this thesis, we analyse massless fermion creation by time-dependent boundaries in (1+1)-dimensional flat spacetimes. We consider two distinct senses in which the boundaries are said to be time-dependent. On one hand, we study a boundary which remains at rest with respect to a family of inertial observers but imposes a time-dependent boundary condition. On the other hand, we study a boundary that moves along a timelike trajectory while imposing a time-independent boundary condition, that is the MIT bag boundary condition. In both cases, we calculate the stress-energy tensor of the spinor field describing the fermions, renormalised via the point-splitting method, and the response of an inertial Unruh-DeWitt detector coupled linearly to the scalar density of the field. Throughout our analysis, we compare our results to those readily available in the literature for a massless scalar field in similar settings.